Propionibacterium acnes overabundance and natural killer group 2 member D system activation in corpus‐dominant lymphocytic gastritis. Issue 4 (21st October 2016) - Montalban‐Arques, Ana; Wurm, Philipp; Trajanoski, Slave; Schauer, Silvia; Kienesberger, Sabine; Halwachs, Bettina; Högenauer, Christoph; Langner, Cord; Gorkiewicz, Gregor
Abstract: Corpus‐dominant lymphocytic gastritis (LyG) is characterized by CD8 + T‐cell infiltration of the stomach epithelium by a so far uncharacterized mechanism. Although Helicobacter pylori is typically undetectable in LyG, patients respond to H. pylori antibiotic eradication therapy, suggesting a non‐ H. pylori microbial trigger for the disease. Comparative microbiota analysis of specimens from LyG, H. pylori gastritis and healthy controls precluded involvement of H. pylori in LyG but identified Propionibacterium acnes as a possible disease trigger. In addition, the natural killer group 2 member D (NKG2D) system and the proinflammatory cytokine interleukin (IL)‐15 are significantly upregulated in the gastric mucosa of LyG patients, and gastric epithelial cells respond to microbe‐derived stimuli, including live P. acnes and the microbial products short‐chain fatty acids, with induction of NKG2D ligands. In contrast, H. pylori infection does not activate or even repress NKG2D ligands. Together, our findings identify P. acnes as a possible causative agent for LyG, which is dependent on the NKG2D system and IL‐15 activation. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.